KONSEP RUKYAH AL-HILAL PERSFEKTIF HADIS NABI SAW - alamsyah; Zulfahmi Alwi; Abd. Rahman Sakka; Erty Rospyana Rufaida (Syakhsia Jurnal Hukum Perdata Islam, 2023)
This paper aims to examine the concept of rukyah al hilal by using the approach of the hadiths of the Prophet saw. As a second source of law. This study is of a literary nature, namely by looking for several sources of hadith from the book of Jami' al hadith an-Nabawi with the analysis used is content analysis. The findings of this study reveal that the understanding of the scholars in understanding the Prophet's hadith about Rukyah al Hilal has differences. The diversity of pronunciations provides several meanings in understanding and using the hadith, thus triggering differences of opinion among the scholars. This difference interprets the word Rukyah axiologically as a method for obtaining new moon data at the beginning of the month so that in understanding it there are three methods, namely the Rukyah method, the reckoning method, and the Isti'mal method. Thus, it becomes an obligation that must be carried out by every Muslim to try to find out the new moon, either through direct observation (ru'yat al-hilal), or using the reckoning method for people who have the expertise and ability to perform calculations or use reckoning. if the hilal is not conclusively known, then the people fall into a doubt on that day, the Prophet forbade fasting on the day that is in doubt, it is considered committing disobedience